Efektivitas Pestisida Alami Berbahan Dasar Daun Sirsak Pada Hama Tanaman Terung - Debora Zega, Novita; Lase, Edwin Kaskar Jaya; Hura, Jul Krisman; Gulo, Murniwati (CV. SINAR HOWUHOWU, 2024)
This research evaluates the effectiveness of soursop leaf extract (Annona muricata) as a natural pesticide in controlling pests on eggplant plants (Solanum melongena). The use of natural pesticides is an environmentally friendly alternative to reduce the negative impact of chemical pesticides on the environment and human health. Soursop leaf extract is obtained through a manual crushing method without solvents and applied directly to eggplant plants infected with pests, especially aphids (Aphididae) and fruit caterpillars (Leucinodes orbonalis). Observations were made within 24 hours to assess changes in pest populations after application. The results of the study showed that soursop leaf extract was able to reduce the pest population significantly, with the majority of pests experiencing disturbances in their feeding activity or death after treatment. The effectiveness of this natural insecticide is thought to come from the content of bioactive compounds such as acetogenin, flavonoids and alkaloids which play a role in inhibiting pest metabolism. Although initial results show positive potential, further research is needed to test its long-term effectiveness and impact on eggplant plant growth and productivity. This study contributes to the development of more sustainable pest control methods in organic farming systems.